2014
DOI: 10.3390/ijms151223332
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis to Reveal Genes Involved in Wheat Hybrid Necrosis

Abstract: Wheat hybrid necrosis is an interesting genetic phenomenon that is found frequently and results in gradual death or loss of productivity of wheat. However, the molecular basis and mechanisms of this genetic phenomenon are still not well understood. In this study, the transcriptomes of wheat hybrid necrosis F1 and its parents (Neimai 8 and II469) were investigated using digital gene expression (DGE). A total of 1300 differentially expressed genes were identified, indicating that the response to hybrid necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…NBS-LRR activation results in an elevated immune response, characterized by the activation of defense-associated genes and the generation of ROS and hypersensitive responses (Spoel and Dong, 2012). In our present study, we found that autoimmunity was associated with hybrid lethality, as has been reported in a number of previous studies (Hatano et al , 2012; Chen et al , 2014; Zhang et al , 2014). Based on our experimental and transcriptome data, the mechanism for induction of autoimmunity and plant death by Le 4 in the interspecific F 1 hybrid between R4-4 and upland cotton is illustrated in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…NBS-LRR activation results in an elevated immune response, characterized by the activation of defense-associated genes and the generation of ROS and hypersensitive responses (Spoel and Dong, 2012). In our present study, we found that autoimmunity was associated with hybrid lethality, as has been reported in a number of previous studies (Hatano et al , 2012; Chen et al , 2014; Zhang et al , 2014). Based on our experimental and transcriptome data, the mechanism for induction of autoimmunity and plant death by Le 4 in the interspecific F 1 hybrid between R4-4 and upland cotton is illustrated in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Total RNA purity and concentration of each sample were measured using the NanoDrop 2000 (Thermo Scientific, Wilmington, DE, USA), and RNA integrity then assessed with the RNA Nano 6000 Assay Kit of the Agilent Bioanalyzer 2100 system (Agilent Technologies, Santa Clara, CA, USA). Only those samples with an RNA integrity number (RIN) ≥ 7 were retained for subsequent analysis 36 .…”
Section: Methodsmentioning
confidence: 99%
“…ABP actin-binding protein (e.g., formin), cis-regulatory elements: ABRE ABA-responsive element, DRE/CRT dehydration-responsive element/C-repeat, MYBR/ MYCR myeloblastosis oncogene/myelocytomatosis oncogene recognition element, NACR non-aggressive challenge responsive element, CK cytoskeleton, CMBP cytoskeleton-membrane-bound polysomes (cytomatrix-bound polysomes), CRT calreticulin, CW cell wall, DAG diacylglycerol, ER endoplasmic reticulum, MF actin microfilament, PM plasma membrane, R potential ABA receptor, and RER rough endoplasmic reticulum. A detailed description can be found in the text Acta Physiol Plant (2017) 39:190 Page 13 of 18 190 Lyzenga and Stone 2012;Zhang et al 2014). According to Yan et al (2000), ubiquitin-specific proteases (USPs)) play a host of important roles in the ubiquitin/26S proteasome pathway by: (1) releasing of free ubiquitins from their translation products, (2) recycling of ubiquitin during degradation of the target compound, which involves the removal of ubiquitin from peptide fragments and splitting of multiubiquitin chains, and/or (3) removing ubiquitins from conjugates before the degradation of the target compound.…”
Section: Protein Turnovermentioning
confidence: 99%